Larval nematodes found in amphibians from northeastern Argentina - Gonzalez, Cynthya Elizabeth (2010)
Five species of amphibians, Leptodactylus podicipinus, Scinax acuminatus, S. nasicus, Rhinella fernandezae and Pseudis paradoxa, were collected in Corrientes province, Argentina and searched for larval nematodes. All larval nematodes were found as cysts in the serous of the stomach of hosts. Were identified one superfamily, Seuratoidea; one genus, Spiroxys (Superfamily Gnathostomatoidea) and one family, Rhabdochonidae (Superfamily Thelazioidea). We present a description and illustrations of these taxa. These nematodes have an indirect life cycle and amphibians are infected by consuming invertebrate, the intermediate hosts. The genus Spiroxys and superfamily Seuratoidea were reported for the first time for Argentinean amphibians.